The structure of an LIM-only protein 4 (LMO4) and Deformed epidermal autoregulatory factor-1 (DEAF1) complex reveals a common mode of binding to LMO4. - Soumya Joseph (Public Library of Science (PLoS), 2014)
LIM-domain only protein 4 (LMO4) is a widely expressed protein with important roles in embryonic development and breast cancer. It has been reported to bind many partners, including the transcription factor Deformed epidermal autoregulatory factor-1 (DEAF1), with which LMO4 shares many biological parallels. We used yeast two-hybrid assays to show that DEAF1 binds both LIM domains of LMO4 and that DEAF1 binds the same face on LMO4 as two other LMO4-binding partners, namely LIM domain binding protein 1 (LDB1) and C-terminal binding protein interacting protein (CtIP/RBBP8). Mutagenic screening analysed by the same method, indicates that the key residues in the interaction lie in LMO4LIM2 and the N-terminal half of the LMO4-binding domain in DEAF1. We generated a stable LMO4LIM2-DEAF1 complex and determined the solution structure of that complex. Although the LMO4-binding domain from DEAF1 is intrinsically disordered, it becomes structured on binding. The structure confirms that LDB1, CtIP and DEAF1 all bind to the same face on LMO4. LMO4 appears to form a hub in protein-protein interaction networks, linking numerous pathways within cells. Competitive binding for LMO4 therefore most likely provides a level of regulation between those different pathways.